What Is The Status Of Indonesiaâ€™s E-Procurement? - NURMANDI, ACHMAD (Jurnal Studi Pemerintahan, 2013)
E-procurement is an important intrument toprevent corruption in goods and servicesprocurement budget. Indonesia has beenimplementing the e-procurement project since2008 based on Presidential Decree. Presidenthas stipulating annual order (presidentialinstruction) has to be obey by all ministries andlocal governments to procure their budgetthrough r-procurement mechanism. However,untill 2012 fiscal year, this research found thatonly around 10.26% of central governmentinstitution procurement budget, includingministries and 21,10% of local governmentprocurement budget did procure through eprocurementmethod. This research concludedthat regulation, leadership and procurementintitution are challanging factors to makeâ€œstatus quoâ€ e-procurement.